The influence of meteorological parameters in the generation of energy in photovoltaic panels: A case study of Smart Campus Facens, SP, Brazil - Camargo Francisco, Ana Carolina; De Miranda Vieira, Henrique Ewbank; Romano, Regiane Relva; Monteiro Masalskiene Roveda, Sandra Regina [UNESP] (FapUNIFESP (SciELO), 2019)
Although it does not have a universally accepted definition, the concept of smart cities is increasingly being discussed. With the significant increase in the percentage of the population living in cities and the consequent increase in the use of resources, new city models are designed so such growth can be sustainable. Energy is one of the key resources needed by man, and new forms of energy generation must be considered. Due to the Brazilian geographic conditions, the use of photovoltaic energy seems to be an excellent option, but today it corresponds to approximately 2% of the total Brazilian energy. This work aimed to relate how the meteorological conditions influence the energy generation of photovoltaic panels to allow the creation of tools that identify regions with high potential of photovoltaic energy generation. The meteorological variables were considered as independent variables of the proposed model, which sought to explain the dependent variable Energy. The results demonstrated a potential generation of photovoltaic solar energy in several places in Brazil since the incidence of solar radiation was identified as the variable that most explains the energy generated and the country has high rates of this variable in all its extension.
Influência de parâmetros meteorológicos na geração de energia em painéis fotovoltaicos: Um caso de estudo do Smart Campus Facens, SP, Brasil
Keywords: Photovoltaic energy; Smart city; Sustainability